Searching for Africa in Brazil : Power and Tradition in Candomblé - Capone, Stefania (Book collections on Project MUSE., 2010)
Analyzes the politics of the "Africanness" of Afro-Brazilian religion, focusing on the conflicts and interplay between academics and practitioners over the past century